Determination of alpha-2-MRAP gene polymorphisms innephrolithiasis patients - Mehde, Atheer Awad; Mehdi, Wesen Adel; Yusof, Faridah; Ahmad Raus, Raha; Zainal Abidin, Zaima Azira; Ghazali, Hamid; Abd Rahman, Azlina (Elsevier B.V., 2017)
Background